Clay Science and Technology 2021
DOI: 10.5772/intechopen.93813
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Perspectives of Clay-Based Tailings in the Mining Industry

Abstract: The mining industry faces a significant problem in regions with water scarcity and has had to put in place new strategies to preserve its environmental and economic sustainability. An attractive option in recent years has been the direct use of seawater, avoiding the construction of reverse osmosis plants to desalinate. But, some operational complexities are the subject of discussion and research for engineers; for example, the difficulties by the high presence of complex gangues like clays and the location of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In this context, it is interesting to compare what happens at pH 8 since it is a relevant condition of what happens in the mining industry. It is shown that seawater can create rheological problems in clay pulps, which is a detriment to the mineral processing operations [14,19,33]. Rheological modifiers may be applied in order to reduce the value of the rheological parameters, which is achieved through reagents that stabilize the pulp.…”
Section: Yield Stress Of Kaolin Slurriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is interesting to compare what happens at pH 8 since it is a relevant condition of what happens in the mining industry. It is shown that seawater can create rheological problems in clay pulps, which is a detriment to the mineral processing operations [14,19,33]. Rheological modifiers may be applied in order to reduce the value of the rheological parameters, which is achieved through reagents that stabilize the pulp.…”
Section: Yield Stress Of Kaolin Slurriesmentioning
confidence: 99%
“…Meanwhile, the associations EF and EE form a three-dimensional structure, known as a house of cards, that increases the fraction of apparent suspension volume [16]. What happens with the fine particles and clays is essential for mineral processing, considering that they have a relevant impact on solid-liquid separation and make the rheological behavior of concentrated slurries more complex [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it is difficult to anticipate whether a saline medium will be beneficial or detrimental to particle flocculation. Therefore, it is essential to improve our understanding of molecular-scale phenomena, because the phenomena that ultimately determine the macroscopic properties of a suspension and are of industrial interest, such as the sedimentation rate, the quality of water recovered in a thickener, the underflow density, or the rheological properties of the underflow, occur at the molecular level [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors that can influence the rheological properties of a material, including its type, mineralogy, moisture content, pH, temperature, salinity, and shear rate history [23], Jeong, [24,25]. Apart from dependency on these properties, a close relation of mudflow with liquidity index and Atterberg's limits has been reported by a few researchers [25][26][27].…”
Section: Introductionmentioning
confidence: 99%